IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MAN KOTA BANJARMASIN - Muhdi, Muhdi; Suraijiah, Suraijiah; Ihsan, M. Adli Nurul; Emroni, Emroni (DARRIS: Jurnal Pendidikan Madrasah Ibtidaiyah, 2024)
Abstract: In the PAI learning process, the implementation of the independent curriculum is seen in the educational approach that provides flexibility for students to be more active in managing the learning process according to their interests, talents, and needs. With this process, students are led to gain more life skill-based experiences within a framework of independence. The implementation of the independent curriculum in PAI learning at MAN Kota Banjarmasin has provided many very valuable experiences for the future of students as pious people who function as khalifatullah on the surface of the earth. This is due to the implementation of the independent curriculum in accordance with its implementation procedures, namely: The implementation process is preceded by a diagnostic assessment carried out on cognitive and non-cognitive, the non-cognitive is carried out at the beginning of the semester by the BK team to become the basis of their knowledge. While the cognitive teacher carries it out at the beginning of learning such as the formative assessment pretest, for the summative it has been implemented, there is a mid-semester summative, this semester's final summative for assessment. In terms of learning, it has been differentiated both in differentiating content by providing a variety of variations of learning materials, differentiating products after the assessment. This is what then led to the successful implementation of P 5 at the end of the activity. Keyword: Implementation, Independent Curriculum, Islamic Religious Education. Abstrak: Dalam proses pembelajaran PAI, implementasi kurikulum merdeka terlihat pada pendekatan pendidikan yang memberikan fleksibilitas kepada siswa untuk lebih aktif turut mengatur proses pembelajaran sesuai dengan minat, bakat, dan kebutuhan mereka. Dengan proses seperti ini siswa digiring untuk lebih banyak menimba pengalaman berbasis life skill dalam bingkai kemandirian. Implementasi kurikulum merdeka dalam pembelajaran PAI di MAN Kota Banjarmasin telah memberikan banyak pengalaman yang sangat berharga untuk masa depan siswa sebagai insan yang bertaqwa yang berfungsi sebagai khalifatullah di permukaan bumi. Hal ini disebabkan oleh implimentasi Kurikulum merdeka yang sesuai dengan prosedur pelaksanaannya, yakni: Proses implementasi didahului oleh adanya assesment diagnostik dilakukan pada kognitif dan non kognitif, yang non kognitif dilakukan di awal semester oleh tim BK untuk menjadi dasar pengetahuannya. Sedangkan yang kognitif guru melaksanakannya di awal pembelajaran seperti Pretest asessment formatifnya, untuk sumatif sudah dilaksanakan ada sumatif tengah semester, sumatif akhir semester ini untuk penilaian. Dalam hal pembelajaran sudah berdiferensiasi baik pada berdiferensiasi konten dengan menyediakan berbagai macam variasi materi pembelajaran, berdiferensiasi prodak pada setelalah penilaian. Inilah yang kemudian menghantarkan suksesnya pelaksanaan P 5 di akhir kegiatan. Kata Kunci: Implementasi, Kurikulum Merdeka, Pendidikan Agama Islam.